1981
DOI: 10.1210/endo-109-4-1150
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Renin in Trophoblasts in Human Chorion Laeve at Term Pregnancy*

Abstract: It is known that renin is present in fetal membranes, with the highest concentration in the chorion laeve (reflected chorion). The purpose of this study was to identify and localize renin in human chorion laeve. Indirect immunofluorescent analysis, using antiserum against pure human kidney renin, revealed a single layer of cells in the chorion with strongly positive fluorescence. The presence of atrophic villi in this layer together with other morphological evidence indicate that the cells which are positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 14 publications
0
26
0
1
Order By: Relevance
“…Detection of renin gene expression in the present study ultimately identified human decidua as a major source of renin in the uteroplacental unit. Previous studies have suggested a seemingly ubiquitous production of renin by uterine and placental tissues, leading to confusion regarding the source and physiologic role of tissue renin in pregnancy (6,8,25,26). We examined renin gene expression in various tissues in the uteroplacental unit to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of renin gene expression in the present study ultimately identified human decidua as a major source of renin in the uteroplacental unit. Previous studies have suggested a seemingly ubiquitous production of renin by uterine and placental tissues, leading to confusion regarding the source and physiologic role of tissue renin in pregnancy (6,8,25,26). We examined renin gene expression in various tissues in the uteroplacental unit to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Most other tissues that have been found to express the renin gene apparently release only prorenin [ 12,14,[20][21][22][23][24][25][26][29][30][31]. These data could imply that the prorenin processing enzyme has a highly restricted tissue distribution; however, the prorenin synthesized by the transfected AtT-20 cells was cleaved to active renin at the natural cleavage site (documented by amino terminal sequencing), and the release of renin was regulated by the same stimulus (cAMP; in this case, 8Br-cAMP) that promotes the release of renal renin [32].…”
Section: Post-transcriptional Events In Renin Gene Expressionmentioning
confidence: 99%
“…The gene is most actively expressed in the renal juxtaglomerular cells, but there are lower levels of expression in the adrenal glomerulosa, testicular leydig cells, ovary, and anterior and intermediate pituitary. In the human, expression was detected in placental cells [30,31 ]. (The specific cell type has not yet been rigorously established.)…”
Section: Introductionmentioning
confidence: 99%
“…Renin has also been suggested to be synthesized in the placenta because of the presence of renin activity in the homogenates of the placental tissues or in the medium of cultured explants from the placenta (Symonds et al, 1968;Warren et al, 1982). Furthermore, Poisner et al localized renin in the chorion by immunohistochemistry (Poisner et al, 1981). However, these studies have only demonstrated the presence of renin activity or renin-like substance in the placenta, rather than its synthesis within the placenta.…”
mentioning
confidence: 99%